Climate Change Impacts and Women's Livelihood : Vulnerability in Developing Countries - Momtaz, Salim; Asaduzzaman, Muhammad; Taylor & Francis (Boca Raton, FL : Routledge, 2018)
Very few studies have been conducted to explore the vulnerability of women in the context of climate change. This book addresses this absence by investigating the structure of women's livelihoods and coping capacity in a disaster vulnerable coastal area of Bangladesh.The research findings suggest that the distribution of livelihood capitals of vulnerable women in rural Bangladesh is heavily influenced by several climatic events, such as cyclones, floods and seasonal droughts that periodically affect the region. Women face several challenges in their livelihoods, including vulnerability to their income, household assets, lives and health, food security, education, water sources, sanitation and transportation systems, because of ongoing climate change impacts. The findings have important policy relevance for all involved in disaster and risk management, both within Bangladesh and the developing countries facing climate change impacts.Based on the research findings, the book also provides recommendations to improving the livelihoods of women in the coastal communities. This book will appeal to academics, researchers and professionals in environmental management, gender and development, and climate change governance looking at the effects of and adaptation to climate change, gender issues and natural disaster management strategies.
1. Introduction 1.1 Background to the study 1.2 Rationale for this book 1.3 Layout of the book References 2. Climate Change Impacts and Women in Bangladesh 2.1 Background information on Bangladesh 2.1.1 Geographical location of Bangladesh 2.1.2 Weather and seasons in Bangladesh 2.1.3 Demography and over-population in Bangladesh 2.1.4 Poverty and inequality in Bangladesh 2.2 Climate change and Bangladesh 2.2.1 Cyclones and storm surges 2.2.2 Sea level rise 2.2.3 Floods and flooding 2.2.4 Salinity 2.2.5 Drought 2.3 The status of women in rural Bangladesh 2.4 Climate change impact on womens livelihood 3. Vulnerability and Sustainable Livelihood Framework: Methodological Considerations 3.1 The Sustainable Livelihood Framework (SLF) 3.1.1 Core concepts of the Sustainable Livelihood Framework 3.1.2 Modelling the Sustainable Livelihoods Framework (SLF) 3.1.3 Application of the Sustainable Livelihood Framework (SLF) around the world and its relevance to this study 3.2 Understanding and assessing vulnerability 3.2.1 Vulnerability assessment 3.2.2 The Disaster Crunch Model 3.2.3 The Livelihood Vulnerability Index (LVI) 3.2.4 LVI-IPCC: IPCC framework approach 3.3 Selection of the study area 3.4 Research design 3.4.1 Data sources 3.4.2 Sampling procedure 3.5 Data collection 3.5.1 Household surveys through personal interviews 3.5.2 Focus group discussion (FGD) 3.5.3 Key informant interviews 3.5.4 Direct observation through a transect walk 3.6 Data Analysis 3.6.1 Quantitative analysis 3.6.1.1Calculation of LVI 3.6.1.2 Calculation of IPCC-LVI 3.6.1.3 Vulnerability spider diagram and vulnerability triangle 3.6.2 Qualitative analysis 3.7 Conclusion 4. An Overview of the Study Area 4.1 Structure of administrative units in Bangladesh 4.2 Outline of the study area 4.3 Shyamnagar upazila at a glance 4.4 The Sundarbans: a part of livelihood of the community in the study area 4.5 The severe impacts of Cyclone Aila 4.6 Observations of the study area by the researcher 4.7 Conclusion 5. Livelihood Capitals of Women against a Background of Disaster 5.1 Human capital 5.1.1 Age structure 5.1.2 Educational status 5.1.3 Marital status 5.1.4 Occupational status 5.1.5 Occupational status of the household head 5.1.6 Daily workload of participants 5.2 Natural capital 5.2.1 Land 5.2.2 Water sources 5.2.3 Forestry resources 5.3 Financial capital 5.3.1 Income structure 5.3.2 Expenditure structure 5.3.3 Balance of income and expenditure 5.3.4 Credit availability to participants 5.4 Social capital 5.4.1 Socio-demographic profile 5.4.1.1 Family size and gender composition 5.4.1.2 Dependency ratio 5.4.1.3 Religion 5.4.2 Social networking 5.4.2.1 Migration to other places 5.4.2.2 Networking with local government organizations 5.5 Physical capital 5.5.1 Housing conditions 5.5.2 Productive assets structure 5.5.3 Condition of sanitation facilities 5.6 Conclusion 6. Vulnerability of Womens Livelihoods and the Coping Mechanisms to Address Climate Change Impacts 6.1 The progression of womens vulnerability 6.2 Climate change and womens vulnerability 6.2.1 Income vulnerability 6.2.2 Vulnerability in household assets 6.2.3 Vulnerability of lives and health 6.2.4 Vulnerability of food security 6.2.5 Vulnerability of education 6.2.6 Vulnerability in relation to water sources 6.2.7 Vulnerability in relation to sanitation 6.2.8 Vulnerability in relation to shelters and security during times of disaster 6.2.9 Vulnerability in communication and transportation 6.3 Coping strategies of women against climatic events 6.3.1 Reduced food intake in and after times of disaster: A common practice 6.3.2 Selling assets: The foremost strategy to adapt to adverse situations 6.3.3 Receiving credit: A most demanding adaptation option 6.3.4 Using savings: The firsthand option for adaptation 6.3.5Alternative livelihoods: A sustainable adaptation option 6.3.6 Using a Vulnerable Group Development (VGD) card: A government initiative 6.3.7 Homestead gardening and poultry rearing: An option that women are comfortable with 6.4 Accessibility of women to major welfare facilities 6.5 Conclusion 7. The Livelihood Vulnerability Index: A Pragmatic Approach to Measuring Vulnerability 7.1 Components of livelihood capitals 7.2 Vulnerability index of human capital 7.3 Vulnerability index of natural capital 7.4 Vulnerability index of financial capital 7.5 Vulnerability index of social capital 7.6 Vulnerability index of physical capital 7.7 Composite Livelihood Vulnerability Index (LVI) 7.8 Presentation of the IPCC-LVI 7.9 Conclusion 8. Conclusion 8.1 Summary of contribution 8.2 Research Implications 8.3 Future directions
OCLC-licensed vendor bibliographic record.
Keywords: SOCIAL SCIENCE / Human Geography; climate and development; climate change; climate change and gender; climate change and women; climate change impact; climate change vulnerability; climate impact; development geographies; development studies; environmental issues; environment and vulnerability; women and development; Climatic changes -- Developing countries; Women -- Employment -- Developing countries